ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM KEPUTUSAN PEMBELIAN PRODUK FASHION SECARA ONLINE (STUDI KASUS PADA KARYAWAN HAPEWORLD BANJARMASIN) - Rizki Amalia Afriana; Nurul Fijriana (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2021)
Abstract, The purpose of this research is to analyze and find out among cultural, social, personal, and psychological factors, which factors most influence consumers when deciding to buy fashion products online. The population is Hapeworld employees who have bought fashion products online as many as 40 people. By using Arikunto's theory, the samples taken were all populations, namely 40 people. The method used is a quantitative method. Collecting data in the form of distributing questionnaires. The data processing in this study used the SPSS program and the analysis tests carried out were the research instrument test, the classical assumption test and the hypothesis test. The results of research shows that cultural, social, personal, and psychological factors simultaneously have a significant effect on purchasing decisions for fashion products online. Partially, social factors and psychological factors have a significant effect, while cultural factors and personal factors do not have a significant effect on purchasing decisions for fashion products online. The most dominant factor influencing online purchasing decisions is psychological factors.